Effectiveness of smartphone application–based self‐management interventions in patients with type 2 diabetes: A systematic review and meta‐analysis of randomized controlled trials. (29th July 2021) - He, Qianyu; Zhao, Xiaoyan; Wang, Yarui; Xie, Qinqin; Cheng, Li
Abstract: Aims: To synthesize evidences on smartphone application–based intervention and determine its effectiveness on glycaemic control, self‐management behaviours, psychological well‐being, quality of life and cardiometabolic risk factors. Design: A systematic review and meta‐analysis of randomized controlled trials (RCTs). Data sources: Major English and Chinese electronic databases were searched from January 2008 to January 2021, including PubMed, Web of Science, Embase, Cochrane Central Register of Controlled Trials, Google Scholar, China National Knowledge Infrastructure (CNKI), Wanfang and Sinomed. Review methods: RCTs were screened and selected if they used smartphone applications to support patients in the self‐management of diabetes. Data extraction and methodological assessment were performed by two reviewers independently. Meta‐analysis was performed to pool the intervention effect on outcomes of interest using RevMan 5.3. Results: Across 19 included trials involving 2585 participants, smartphone application–based interventions were associated with a clinically and statistically significant reduction of glycated haemoglobin (HbA1c). Beneficial effects were also observed in participants' behavioural performance, especially in medication adherence. Intervention effects on psychological status, quality of life and cardiometabolic risk factors were nonsignificant. Subgroup analysis showed interactive approach with medium frequency or flexible facilitator–patient interaction induced a larger effect on HbA1c reduction. Besides, patients with baseline HbA1c ≥9% benefited more than those with HbA1c <9% from the use of smartphone applications. Conclusions: Smartphone application–based diabetes self‐management intervention could optimize patients' glycaemic control and enhance participants' self‐management performance. Further endeavour is required to examine the long‐term effects and cost‐effectiveness of smartphone application–based intervention before promoting the adoption and dissemination of such intervention. Impact: This review supports the potential of smartphone application–based intervention as effective approach to optimize glycaemic control and promote self‐management engagement among patients with type 2 diabetes. Suggestions for future research and practice are provided and discussed.